A novel risk score to predict survival in advanced heart failure due to cardiac amyloidosis - Kreußer, Michael; Volz, Martin J.; Knop, Benjamin; Ehlermann, Philipp; Schmack, Bastian; Ruhparwar, Arjang; Hegenbart, Ute; Schönland, Stefan; Katus, Hugo; Raake, Philip (Clinical research in cardiology, 2020)
Cardiac amyloidosis, caused by deposition of immunoglobulin light chains (AL) or transthyretin (ATTR), carries a poor prognosis. Established risk scores for amyloidosis may not predict outcomes in those patients who develop advanced heart failure and who are potential candidates for heart transplantation. Here, we aimed to identify predictive parameters for patients with severe heart failure due to amyloidosis.